Clinical diagnosis of Binswanger's disease. - Bennett, D A (1990)
To aid in the prospective study of Binswanger's disease, a poorly understood form of vascular dementia, a standardised criteria for its antemortem diagnosis was proposed. These criteria include dementia, bilateral radiological abnormalities on computed tomography (CT) or magnetic resonance imaging (MRI), and at least two of the following three clinical findings: A) a vascular risk factor or evidence of systemic vascular disease; B) evidence of focal cerebrovascular disease; and C) evidence of "subcortical" cerebral dysfunction. These criteria were validated in two ways. First, by retrospectively applying them to a series of 30 demented patients with various pathological diagnoses. Second, by prospectively applying them to a series of 184 patients with clinically typical Alzheimer's disease. The sensitivity and specificity of the criteria appear adequate for use in clinical research.